2016
DOI: 10.1007/s12574-016-0308-2
|View full text |Cite
|
Sign up to set email alerts
|

Fetal echocardiography for early detection of congenital heart diseases

Abstract: Fetal echocardiography can effectively identify abnormal hearts and has enhanced prenatal detection of CHD. The concern in the Indian scenario is the late referrals, lack of follow-up, and financial difficulties, all of which conspire against the chance of the fetus with heart disease getting appropriate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 13 publications
3
17
0
Order By: Relevance
“…The average gestational week in the first evaluation was 24±4.2 in our study. In other studies, fetal echocardiography was performed in similar gestational weeks (7,8). The most common reason for admission to our clinic was the suspicion of CHD in accordance with the literature (7,8).…”
Section: Discussionsupporting
confidence: 60%
“…The average gestational week in the first evaluation was 24±4.2 in our study. In other studies, fetal echocardiography was performed in similar gestational weeks (7,8). The most common reason for admission to our clinic was the suspicion of CHD in accordance with the literature (7,8).…”
Section: Discussionsupporting
confidence: 60%
“…In this study, the HLHS forms 9.4% of CHDs. Chitra et al reported this rate as 15% [9]. This difference may result from that our centre does not have a pediatric cardiovascular unit which could have great importance for newborn survival after birth and this condition might affect parents' preference for choosing the centre for delivery.…”
Section: Discussionmentioning
confidence: 89%
“…This is not in agreement with previous studies showing a correlation between fetal EIF and congenital heart diseases. 10 , 21 , 22 Currently, karyotyping, FISH, multiplex ligation-dependent probe amplification (MLPA) and CMA are major tools used to detect the chromosomal abnormality in fetuses with ultrasound soft markers. 23 , 24 Chromosomal karyotype analysis is limited by the success rate of culture and the resolution, while CMA is effective to detect abnormality of chromosomal fragments with >1 kb in size and microduplication and microdeletion syndromes.…”
Section: Discussionmentioning
confidence: 99%